Soursop Leaf Nanoparticles On Blood Glucose Levels And Ankle Brachial Pressure Index (ABPI) Values In Type-2 Diabetes Mellitus Patients - Samsuri, Taadi; mardiyono, Mardiyono; Rahayu, Umi Margi; Saputri, iken Anggraini Sri (Jurnal Riset Kesehatan, 2023)
Chronic hyperglycemia will cause legs and blood circulation disorders. Treatment with insulin is still quite expensive and with some side effects of oral hypoglycemic drugs. This experience made the management of DM switch to herbal treatment, namely soursop leaves (Annona muricata). The study used a pre and post test control group design with random allocation. Quasy experimental study with a two group pre tpost-testest – post tepost-testst design at 36type-2 DM patients in the Pekalongan City area. Blood glucose levels in the treatment group were measured before and after administration of soursop leaf nanoparticles500 ml/20 gBB 3 times a day for 6 days and 500 mg metformin. Giving soursop leaf nanoparticles at a dose of 500 ml/20 grBW 3 times a day for 6 days is effective on fasting blood glucose levels clinically with a change in value of 65 mg/dL, and has a statistically significant effect on reducing fasting glucose levels (p=0.035).